Vgf is a novel biomarker associated with muscle weakness in amyotrophic lateral sclerosis (ALS), with a potential role in disease pathogenesis - Zhong Zhao, Dale J. Lange, Lap Ho, Sara Bonini, Belinda Shao, Stephen R. Salton, Sunil Thomas, Giulio Maria Pasinetti (International Journal of Medical Sciences, 2008)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects nerve cells in the brain and the spinal cord. Previous proteomic evidence revealed that the content of certain peptide fragments including Vgf-derived peptide aa 398-411 (Vgf398-411) of the precursor Vgf protein in the cerebral spinal fluid (CSF) correctly identified patients with ALS from normal and disease controls. Using quantitative ELISA immunoassay we found that the CSF levels of Vgf decreases with muscle weakness in patients with ALS. In SOD1 G93A transgenic mice, loss of full-length Vgf content in CSF, serum and in SMI-32 immunopositive spinal cord motor neurons is noted in asymptomatic animals (approximately 75 days old) and continues to show a progressive decline as animals weaken. In vitro studies show that viral-mediated exogenous Vgf expression in primary mixed spinal cord neuron cultures attenuates excitotoxic injury. Thus, while Vgf may be a reliable biomarker of progression of muscle weakness in patients with ALS, restoration of Vgf expression in spinal cord motor neurons may therapeutically rescue spinal cord motorneurons against excitotoxic injury.